1995
DOI: 10.1152/jappl.1995.78.4.1555
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 beta and IL-6 induce hyperplasia and hypertrophy of cultured guinea pig airway smooth muscle cells

Abstract: Guinea pig airway smooth muscle (ASM) cells were maintained in a primary tissue culture (passages 1-3). Cells were exposed to human recombinant interleukin-1 beta (IL-1 beta; 20-100 pg/ml) or interleukin-6 (IL-6; 1-4 ng/ml) in the presence of indomethacin (1 microgram/ml) for up to 5 days. Proliferation of ASM cells was assessed with two techniques, direct counting of cells with a hemacytometer and [3H]thymidine incorporation corrected for total protein content. Hypertrophy of ASM cells was assessed by [3H]leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 0 publications
1
39
1
1
Order By: Relevance
“…The increase in smooth muscle mass may be due to several factors, including proliferation of smooth muscle induced by inflammatory mediators [26], cytokines [27] and growth factors [28,29]. It has been suggested that an intrinsic abnormality of smooth muscle may underlie asthma severity, but data are lacking to support this hypothesis.…”
Section: Structural Changesmentioning
confidence: 99%
“…The increase in smooth muscle mass may be due to several factors, including proliferation of smooth muscle induced by inflammatory mediators [26], cytokines [27] and growth factors [28,29]. It has been suggested that an intrinsic abnormality of smooth muscle may underlie asthma severity, but data are lacking to support this hypothesis.…”
Section: Structural Changesmentioning
confidence: 99%
“…Broadly, the substances now implicated in mitogenesis of airway smooth muscle, in addition to the action of serum itself (discussed in [49]), include pro-inflammatory mediators (histamine [46], 5-hydroxytryptamine (5-HT) [50], phenylephrine [51], tachykinins [52], endothelin (ET)-1 [53Ā±56] and leukotriene D 4 [57]), several inflammatory cell-and plasma-derived enzymes (a-thrombin [58], tryptase [59], b-hexosaminidase and b-glucuronidase [60]), polypeptide growth factors (platelet-derived growth factor (PDGF) [61], epidermal growth factor (EGF) [62], fibroblast growth factor-2 (FGF-2) [63] and insulin-like growth factors (IGFs) [64]) and thromboxanes [65]. Pro-inflammatory cytokines (interleukin-1b [66], interleukin-6 [67], and tumour necrosis factor-a [68]) also induce a proliferative response in airway smooth muscle, which is revealed only under conditions of cyclo-oxygenase inhibition [69], in which the production and action of inhibitory prostanoids such as prostaglandin E 2 is limited. Other trophic factors such as altered mechanical stress [70] and reactive oxygen species [71] have also been identified.…”
Section: Mediators Of Airway Smooth Muscle Proliferationmentioning
confidence: 99%
“…Interleukin-6 (IL-6) is a pleiotropic cytokine that is generally considered proinflammatory. It exerts numerous functions, including the induction of pulmonary neutrophil infiltration, airway mucus secretion, lung fibrosis, and hyperplasia and hypertrophy of airway smooth muscle cells (16,19,28,42). Increased production of IL-6 has been observed in the airways of patients with asthma, COPD, ARDS, and VILI (5,11,40,44,54).…”
mentioning
confidence: 99%